Influence of Fire-Flame Temperature and Duration on the Behavior of Reinforced Concrete Beams with Construction Joints (Journal of Engineering, 2024)
Structural members' durability and strength depend on the member’s fire resistance. This study simulates the structural response of a reinforced concrete beam with a construction joint exposed to fire. The commercial finite element software ABAQUS was used to validate the laboratory findings. The testing program tested five reinforced concrete beams with the dimensions of (200x300x2700 mm), having identical reinforcing details and a concrete compressive strength (fc'=35 MPa). These beams had a 45° angled connection at the center. Four beams were exposed to fire flames at two temperature levels (600 °C and 800 °C) and for 1.0 and 2.0 hr. periods, respectively. The fifth beam is the control beam that was not exposed to fire. Laboratory results show that the worst exposure on the beam’s construction joint was at 800 °C with an exposure period of 2 hrs. This exposure reduces the bond between the joint’s two surfaces, creating a slipping effect in which disconnection occurs after loading. After 1 and 2 hours of exposure to fire at 600 °C, the residual flexural strength was 85% and 72% of that of the control beam, respectively.  Whereas, beams exposed to fire for 1 and 2 hours at 800 °C showed flexural strengths lower than the control beam at 41% and 28%, respectively.  Regarding the modulus of elasticity and compressive strength, they both showed residual values of (63.5, 59.2, 50.9, and 47%), and (28, 25, 19, and 16%), respectively.